The Effect of Hyperbaric Oxygen Therapy on Male Infertility - Sandhi Cahyani, Maria Benedictin; Purwanto, Bambang (Universitas Airlangga, 2025)
Background : Infertility is one of the major health concern on a global health problems. This is because around 15% of couples worldwide have difficulty conceiving. Along with advances in science and technology, researchers are trying to find and develop new treatment methods. One of the alternative therapies for infertility is hyperbaric oxygen therapy (HBOT). Reviews : Infertility is a reproductive system disease in both men and women, characterized by the inability or failure to conceive after 12 months or more of regular unprotected sexual intercourse. In the management of infertility, HBOT can help improve sperm quality and spermatogenesis, the process of sperm formation, thereby contributing to increased fertilization. In addition, HBOT can increase oxygenation of testicular tissue, thereby increasing normal sperm count and good motility, which are essential for fertilization. Summary : HBOT can improve sperm viability and motility. By increasing vascularization, tissue oxygenation, and improving post-procedure conditions, HBOT may potentially improve fertility outcomes. Keywords : Hyperbaric Oxygen Therapy (HBOT), Male Infertility, Sperm.